Analytical data for Ti, Mo, and Pb in selected nodules from different stations in the Aitutaki Passage - Glasby, Geoffrey P; Thijssen, Theo; Plüger, W L; Friedrich, Günther; Mangini, Augusto; Stoffers, Peter; Dominik, J; Frenzel, G; Andrews, J E; Roonwal, G S (PANGAEA, 2023)
Manganese nodules and crusts from stations of the SO06 expedition (R/V Sonne) in the Aitutaki Passage have been selected for chemical analysis of Ti, Mo and Pb using atomic absorption spectrophotometry. Material has been dried before analysis at 105°C for 72 hrs and results are presented as averages over various size fractions.
Keywords: Geochemistry; manganese micronodule; manganese nodule; ocean; sediment